Mães privadas de liberdade: um olhar psicossocial sobre a maternidade - Pinto, Adriele Vieira de Lima (2021)
Abstract: Maternity in Brazilian prisons is marked by experiences of vulnerabilities and psychological suffering. These aspects are accentuated by the historical invisibility associated with female incarceration, which denies the specificities of women, including issues related to motherhood. In this context, we sought to study the theme through the Social Representation Theory (SRT), which allowed access to the network of senses and meanings, shared by mothers in deprivation of freedom, building a practical and multifaceted knowledge on the subject. In this direction, the following thesis aimed to know the psychosocial aspects interrelated to motherhood in the prison context. Structurally, it was divided into two parts, the first consisting of theoretical chapters and the second consisting of three studies. In the first study, we did a review of the national scientific production, published between 2009 and 2019. 15 articles were selected, analyzed by the Descending Hierarchical Classification (DHC) and the Similitude Analysis, through Iramuteq. The results indicated the recent nature of the productions on the theme, with a main focus on health issues, guarantee/violation of rights, damage to the mother-child relationship and issues related to prenatal care, pregnancy and breastfeeding. The other two empirical studies were guided by SRT. The first empirical study analyzed the Social Representations (SR) of mothers deprived of liberty, based on six evocative words (being a mother, maternity, paternity, family, prison and myself). 52 mothers, aged between 21 and 64 years old (M=33.08; SD=8.71), from the Women's Resocialization Center in João Pessoa, Paraíba, participated in the study. Participants answered the Sociodemographic Questionnaire and the Free Word Association Technique. Data were processed by SPSS (version 21) and Tri-Deux-Mots and interpreted by Factorial Correspondence Analysis. It was observed that the prison context has implications for the production of senses and meanings attributed to different aspects of the life of the mothers in custody. The results indicated consensual representations between being a mother, motherhood, fatherhood and family. Prison was associated with negative stigmatizing experiences and psychological distress. The stimulus myself brought ambiguous elements that manifested engagement and self-punishment. The second empirical study aimed to know the SR about motherhood, elaborated by mothers deprived of freedom. Fifteen mothers, aged between 21 and 44 years old (M=30.47; SD=6.25), who were kept in the same female rehabilitation center in the previous study, participated in the study. They answered the sociodemographic questionnaire and the indepth interview. Data were processed by SPSS (version 21) and Alceste software, and analyzed by CHD. Two main axes of meaning emerged: “Prison and its system of duties and rights” and “Vulnerabilities and the meaning of motherhood”. In them, motherhood was marked by the loss of psychosocial bonds between mother and child. Being a mother was objectified as synonymous with suffering, uncertainty and guilt for the absence of maternal care and separation from children and family members. It is noteworthy that the SR on motherhood in prison acquired different facets that now approached and distanced themselves from the socially disseminated ideal of motherhood. Thus, the maternal condition of mothers in deprivation of liberty leads to the recognition that female imprisonment cannot be considered in isolation, as there will be implications for their family and children and, more broadly, for society. Therefore, it is expected that the results of this thesis help planning social and health practices that are effective for this population and their dependents.